Aprimoramento e avaliação da eficiência de protótipos da armadilha BG-Malária para a captura de adultos de Anopheles darlingi - Moreno de Souza Rodrigues (2013)
Currently the most used and reliable method for monitoring Anopheles mosquitoes is the human landing catch. Recently, the BG-Malaria trap was developed and evaluated in capturing of anophelines presenting promising results. However, the trap had limitations as to the integrity of the insects collected and the attractive used as bait. Thus, this study aimed to: (i) developing a collector tube able to maintain the integrity of the collected insects, (ii) evaluate the response of An. darlingi to different amount of CO2, (iii) test the efficiency of Saccharomyces cerevisiae as bait in traps BG-Malaria and, (iv) compare the new prototype of the trap with human landing catch. The field work was conducted in Belém - PA, Porto Velho and Candeias do Jamari - RO following the experimental Latin square design where the number of repetitions was adjusted according to the experiment. Samples were collected during the first four hours of scotophase (18:00 to 10:00 p.m.) and the data were analyzed using the statistical software R. The results indicated that the best containment system of insects to the trap are made of rigid material, since such damaging a minor amount of insects when compared to the standard (p <0,05). Further, it was found that the amount of CO2 used as attractive does not increase significantly (p> 0.05), the amount of An. darlingicollected in traps BG-Malaria. Traps baited with S. cerevisiae capture significantly more beetles than traps without the addition of CO2 (p <0.5), but are less efficient than traps baited with dry ice (p> 0.05). When compared to the collection by human attraction the new prototype BG-Malaria trap captured significantly fewer insects (p <0,05). Although the new prototype developed showed a improves in the amount of insect damaged, it needs further studies aiming the incorporation of other attractive so the amount of collected mosquitoes can be equal or greater than that observed in human attraction.